Further evidence for altered cerebellar neuronal integrity in schizophrenia - Ende, Gabriele; Hubrich, Petra; Walter, Sigrid; Weber-Fahr, Wolfgang; Kämmerer, Nina; Braus, Dieter F.; Henn, Fritz A. (The American journal of psychiatry, 2005)
OBJECTIVE: The authors’ goal was to investigate the distribution of metabolites and voxel composition in the pons and three cerebellar subregions and compare metabolite integral values and differences in voxel composition between patients with schizophrenia and healthy subjects. METHOD: Proton magnetic resonance spectroscopic imaging was used to study the cerebellum and pons of 14 patients with schizophrenia and 14 healthy comparison subjects. RESULTS: The voxel composition was not significantly different between the groups, but the patients with schizophrenia had significantly lower N-acetylaspartate levels in the cerebellar cortex and vermis. CONCLUSIONS: The lower integral value of N-acetylaspartate in the cerebellar cortex and the vermis of patients with schizophrenia supports the theory of a dysfunctional corticocerebellar-thalamic-cortical circuit in schizophrenia.